Severe COPD cases from Korea, Poland, and USA have substantial differences in respiratory symptoms and other respiratory illnesses - Kim WJ; Yim J; Kim DK; Lee MG; Fuhlbrigge AL; Sliwinski P; Hawrylkiewicz I; Wan ES; Cho MH; Silverman EK (International Journal of COPD, 2017)
Woo Jin Kim,1 Jae-Joon Yim,2 Deog Kyeom Kim,3 Myung Goo Lee,4 Anne L Fuhlbrigge,5 Pawel Sliwinski,6 Iwona Hawrylkiewicz,6 Emily S Wan,7,8 Michael H Cho,7,8 Edwin K Silverman7,8 1Department of Internal Medicine and Environmental Health Center, Kangwon National University Hospital, Chuncheon, 2Department of Internal Medicine, Division of Pulmonary and Critical Care Medicine, Seoul National University College of Medicine, Seoul, 3Department of Internal Medicine, Division of Pulmonary and Critical Care Medicine, Seoul Metropolitan Government-Seoul National University Boramae Medical Center, Seoul National University College of Medicine, Seoul, 4Division of Pulmonary, Allergy and Critical Care Medicine, Hallym University Chuncheon Sacred Heart Hospital, Chuncheon, Korea; 5Division of Pulmonary Sciences and Critical Care Medicine, University of Colorado School of Medicine, Aurora, CO, USA; 62nd Department of Respiratory Medicine, Institute of Tuberculosis and Lung Diseases, Warsaw, Poland; 7Channing Division of Network Medicine, 8Division of Pulmonary and Critical Care Medicine, Brigham and Women’s Hospital, Boston, MA, USA Purpose: Chronic obstructive pulmonary disease (COPD), characterized by irreversible airflow obstruction, is a major cause of morbidity and mortality worldwide. However, geographic differences in the clinical characteristics of severe COPD patients have not been widely studied. Methods: We recruited a total of 828 severe COPD cases from three continents. Subjects in Poland were enrolled by the Institute of Tuberculosis and Lung Diseases in Warsaw; subjects in Korea participated at several university hospitals in Korea; and subjects in USA were enrolled at two clinics affiliated with academic medical centers. All subjects were over the age of 30 with at least 10 pack-years of cigarette smoking history. Cases manifested severe to very severe airflow obstruction with post-bronchodilator forced expiratory volume in 1 second (FEV1) <50% predicted and FEV1/forced vital capacity <0.7. All subjects completed a detailed questionnaire and underwent standardized pre-bronchodilator and post-bronchodilator spirometry. Subjects with known tuberculosis (TB)-associated lung parenchymal destruction were excluded. Univariate and multivariate assessments of the impact of the country of origin on respiratory symptoms and respiratory illness were performed. Results: In both univariate and multivariate analyses, a history of TB (38.7%) and physician-diagnosed asthma (43.9%) were significantly more common in subjects with severe COPD from Korea than USA or Poland, while attacks of bronchitis (64.2%) were more common in subjects with severe COPD from Poland. COPD subjects from Poland had more severe dyspnea (modified Medical Research Council 3.3±1.0) and more frequently reported symptoms of chronic bronchitis (52.2%). A history of TB was also more common in Poland (10.8%) than in USA (0.3%) severe COPD patients. Conclusion: Respiratory symptoms and other respiratory illnesses associated with severe COPD differed widely among three continents. Keywords: COPD, epidemiology, respiratory symptoms, tuberculosis